Promoting Precipitation Technique using Bio-Chemical Grouting for Soil Liquefaction Prevention - Heriansyah Putra; Hideaki Yasuhara; Naoki Kinoshita; Muhammad Fauzan (Institute of Research and Community Outreach - Petra Christian University, 2020)
The applicability of bio-chemical grouting as the environmentally friendly and economically method for liquefaction remediation was evaluated. Several combinations of organic and in-organic precipitations methods were conducted to obtain the optimum grouting solution. Organic precipitation method employs a bio-agent of urease enzyme to dissociate urea into ammonium and carbonate ions. The produced carbonate ions are precipitated as calcite crystals in the presence of calcium ions. Meanwhile, the in-organic methods were performed using chemical compounds only, without the bio-agent. Unconfined compressive strength (UCS) tests were performed to evaluate the applicability of the grouting solutions for improving the soil strength. Grouting solution is injected into the prepared sand samples. The sand samples with a relative density of 50% were treated with one and two PV for 3-day curing times. The experimental results showed that the organic precipitation method produced the high precipitated amount and resulted in the significant improvement in the strength of the treated sand. The presence of the precipitated materials within the grains of soil generated the strength of 272 kPa. The results of this study have elucidated that the organic precipitation method composed of calcium chloride, magnesium sulfate, urea and enzyme of urease may be an alternative soil-improvement technique to prevent the liquefaction susceptibility.